Validity and Reliability of Farra Eye Model as a Surgical Simulator for Capsulorhexis Training: Oral Presentation - Observational Study - Resident - HANIFAH RAHMANI NURSANTI; Julie Dewi Barliana; Syska Widyawati; Faraby Martha; Levina Chandra Khoe (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Various simulation models are available for cataract surgery training. Farra Eye Model, a new cataract surgery simulator, was developed to provide the resident with more affordable options. This study aims to determine the validity and reliability of the Farra Eye Model as a surgical simulator for capsulorhexis training. Methods : A cross-sectional pilot study was performed among ophthalmology residents and consultants to assess face, content, and construct validity of a new surgical simulator. Subjects were divided into novice, intermediate, and expert groups according to their level of expertise. Face and content validity was assessed using a validated questionnaire with a 5-point Likert scale response. Construct validity was done by comparing capsulorhexis performance between the three groups. Two raters assessed performance using capsulorhexis indices in ICO-OSCAR: Phaco assessment tool, number of forceps grabs, and duration of capsulorhexis. Results : A total of 33 subjects were recruited and divided equally into three groups. The overall face validity score was favorable (3.67 ± 0.67). However, the capsule elasticity was rated poor (2.73 ± 1.1) among the intermediate group. The content validity was favorable regarding the overall score (4.15± 0.58) and each assessment component. In the construct validity test, intermediate and expert groups showed better capsulorhexis performance than the novice group on all parameters (p<0.001), with good inter-rater reliability (ICC>0.7). Conclusion : Farra Eye Model has a good face and content validity for capsulorhexis training and is able to differentiate the novice group from intermediate and expert groups. However, it remains a challenge to replicate human lens capsule elasticity.